Thermoregulation, Haematological Profile and Productivity of Holstein Friesian Under Heat Stress at Different Land Elevations - Elmy mariana; Cece Sumantri; Dewi Apri Astuti; Anneke Anggraeni; Asep Gunawan (Buletin Peternakan, 2019)
The purpose of this research was to determine the effect of heat stress on thermoregulation, haematology, and productivity of Holstein Friesian (HF) dairy cows raised in different elevations. A total of 63 HF in a normal lactation period were used in this study. The research was conducted for 3 months during dry season in three different areas, which were at Pondok Ranggon (97 m.a.s.l) which categorized as a lowland, Ciawi (576 m.a.s.l) which categorized as a lower-upland, and Lembang (1241 m.a.s.l) which categorized as an upland. Observation on microclimate aspects which includes environmental temperature (Ta), relative humidity (RH) and Temperature-Humidity Index (THI) was done by recording each variable for every 2 hours starting from 08.00 to 16.00 WIB. The thermoregulation analysis was done based on the given physiological responses which consisted of the skin temperature (Ts), rectal temperature (Tr), body temperature (Tb), heart rate (Hr), respiratory rate (Rr), Heat Tolerance Coefficient (HTC), plasma cortisol level and haematological profile observation. The Ta, Rr, and THI measurements showed that in the lowland and lower-upland, the HF experienced moderate heat stress, while the HF raised in the upland area experienced less heat stress. The results showed that the dairy cows which raised in lowland had the highest HTC, Tr, Ts and Tb (P<0.05) and lowest Hr (P<0.05). All of the physiological and haematological parameters in the three study area showed a normal value.Furthermore, the erythrocyte, Hb and PVC concentration in a lowland raised HF were higher (P<0.05), while the plasma cortisol levels were not significantly different. The milk production of the observed dairy cows in different elevations was significantly different (P<0.05), with the highest milk yields, were found in the upland raised HF (13.1±3.52 kg), followed by the lower-upland (11.3±4.73 kg) and lowland (7.0±3.36 kg). In general, all of the HF raised in different land elevations was exposed to heat stress during dry seasons, even though the cows showed the ability to physiologically adapt and cope with the conditions.